Dominance of wine Saccharomyces cerevisiae strains over S. kudriavzevii in industrial fermentation competitions is related to an acceleration of nutrient uptake and utilization. (10th March 2019) - Alonso‐del‐Real, Javier; Pérez‐Torrado, Roberto; Querol, Amparo; Barrio, Eladio
Summary: Grape must is a sugar‐rich habitat for a complex microbiota which is replaced by Saccharomyces cerevisiae strains during the first fermentation stages. Interest on yeast competitive interactions has recently been propelled due to the use of alternative yeasts in the wine industry to respond to new market demands. The main issue resides in the persistence of these yeasts due to the specific competitive activity of S. cerevisiae . To gather deeper knowledge of the molecular mechanisms involved, we performed a comparative transcriptomic analysis during fermentation carried out by a wine S. cerevisiae strain and a strain representative of the cryophilic S. kudriavzevii, which exhibits high genetic and physiological similarities to S. cerevisiae, but also differences of biotechnological interest. In this study, we report that transcriptomic response to the presence of a competitor is stronger in S. cerevisiae than in S. kudriavzevii . Our results demonstrate that a wine S. cerevisiae industrial strain accelerates nutrient uptake and utilization to outcompete the co‐inoculated yeast, and that this process requires cell‐to‐cell contact to occur. Finally, we propose that this competitive phenotype evolved recently, during the adaptation of S. cerevisiae to man‐manipulated fermentative environments, since a non‐wine S. cerevisiae strain, isolated from a North American oak, showed a remarkable low response to competition.